2018
DOI: 10.1016/j.stemcr.2017.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptionally and Functionally Distinct Mesenchymal Subpopulations Are Generated from Human Pluripotent Stem Cells

Abstract: SummaryVarious mesenchymal cell types have been identified as critical components of the hematopoietic stem/progenitor cell (HSPC) niche. Although several groups have described the generation of mesenchyme from human pluripotent stem cells (hPSCs), the capacity of such cells to support hematopoiesis has not been reported. Here, we demonstrate that distinct mesenchymal subpopulations co-emerge from mesoderm during hPSC differentiation. Despite co-expression of common mesenchymal markers (CD73, CD105, CD90, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…In seminal studies, Cheung et al, [21] generated SMCs from hPSCs through well-defined neural crest, lateral plate and paraxial mesoderm intermediates, and demonstrated that these cells recapitulate origin-specific proliferative and secretory responses to growth factors, cytokines and vasoactive agonists. Other studies by Chin et al, [78], revealed phenotypical and functional heterogeneity within hPSC-derived mesenchymal cells defined by typical PDGFRβ + CD90 + CD105 + CD44 + CD73 + MSC phenotype. CD146 high CD73 high PDGFR − subset within phenotypical MSC population expressed genes associated with hematopoietic stem cell (HSC) niche and supported HSC expansion in vitro .…”
Section: Mb Potential For Cellular Therapiesmentioning
confidence: 93%
“…In seminal studies, Cheung et al, [21] generated SMCs from hPSCs through well-defined neural crest, lateral plate and paraxial mesoderm intermediates, and demonstrated that these cells recapitulate origin-specific proliferative and secretory responses to growth factors, cytokines and vasoactive agonists. Other studies by Chin et al, [78], revealed phenotypical and functional heterogeneity within hPSC-derived mesenchymal cells defined by typical PDGFRβ + CD90 + CD105 + CD44 + CD73 + MSC phenotype. CD146 high CD73 high PDGFR − subset within phenotypical MSC population expressed genes associated with hematopoietic stem cell (HSC) niche and supported HSC expansion in vitro .…”
Section: Mb Potential For Cellular Therapiesmentioning
confidence: 93%
“…Multiple protocols to differentiate hPSCs into mesenchymal stem-like cells (16) and perivascular cells (17)(18)(19) have been described. However, functional differentiation demonstrated that in most cases, hPSC mesodermal derivatives are heterogenous cell populations composed of a mixture of mesodermal progenitors that can be distinguished based on their differentiation potentials (e.g., osteo-/chondro-/ fibro-/adipogenic) and level of expression or lack of expression of characteristic sets of markers (20,21). Additionally, in vitro modifications evolve in long-term cultures, resulting in progressive cell maturation or acquirement of fibroblast-like characteristics (12).…”
Section: Introductionmentioning
confidence: 99%
“…110 In addition, the hPSCs were induced for mesoderm differentiation using OP9 stromal cell coculture or growth factors BMP4, VEGF, and FGF-2. 111 The derived cells coexpressed common mesenchymal markers (CD73, CD90, CD105, and PDGFRb), and a subset of CD146 hi CD73 hi population was identified. It was found that the derived cells provided stromal support of hematopoietic stem cells, which was contact dependent and mediated through high Notch signaling (e.g., Jagged 1) and low Wnt signaling.…”
Section: Mesoderm Inductionmentioning
confidence: 99%